Question:

Ln(y - 7) - ln(7) = x + ln(x), find y. ?

by  |  earlier

0 LIKES UnLike

not sure how to approach this one. thanks.

 Tags:

   Report

5 ANSWERS


  1. ln (y - 7) - ln (7) = x + ln (x)

    Use the quotient property of logarithms.

    ln ( (y - 7) / 7 ) = x + ln (x)

    ln ( (y - 7) / 7 ) - ln (x) = x

    ln ( ( (y - 7) / 7 ) / x ) = x

    ln ( ( (y - 7) / 7 ) * (1/x) ) = x

    ln ( (y - 7) / 7x ) = x

    Take base e raised to the power of both sides.

    e^( ln ( (y - 7) ) / 7x ) = e^(x)

    (y - 7) / 7x = e^(x)

    y - 7 = 7x *e^(x)

    y = 7xe^(x) + 7


  2. ln(y - 7) - ln(7) = x + ln(x)

    [First, move all ln terms to one side]

    ln(y - 7) - ln(7) -  ln(x) = x

    [Now, use ln properties to combine ln terms]

    [Remember division inside the ln can be turned into subtraction outside the ln, and vice versa.]

    ln[(y - 7)/(7x)] = x

    [next take e^ of both sides]

    e^[ln[(y - 7)/(7x)]] = e^x

    [e^ln is equal to one]

    (y - 7)/(7x) = e^x

    [Next, multiply by 7x on both sides]

    (y - 7) = (7x)e^x

    [Lastly, add 7 to both sides]

    y = 7xe^(x) + 7

  3. I found Y its just next to Z

  4. ln(y - 7) - ln(7) = x + ln(x)

    ln((y - 7) / 7)) = x + ln(x)   [property of logarithms]

    e^(ln((y - 7) / 7))) = e^(x + ln(x))   [introduce e as a base]

    (y - 7) / 7 = (e^x)(e^ln(x))   [properties of logarithms and exponents]

    (y - 7) / 7 = (e^x) x   [property of natural logarithms]

    y - 7 = 7(e^x) x   [algebra]

    y = 7(e^x) x + 7   [algebra]

    y = 7(xe^x + 1)   [algebra]


  5. -> Use a law of logartithms

    ln((y-7)/7)=x+lnx

    e^(ln((y-7)/7)=e^(x+lnx)

    (y-7)/7=e^(x+lnx)

    y-7=7e^(x+lnx)

    y=7+7e^(x+lnx)

Question Stats

Latest activity: earlier.
This question has 5 answers.

BECOME A GUIDE

Share your knowledge and help people by answering questions.